Zirconia crucible and method for producing the same

CN118955126BActive Publication Date: 2026-11-03YANTAI HEJING CERAMIC NEW MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411026674.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2026-11-03
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

Existing zirconia crucibles have poor thermal shock resistance, complex preparation processes, and low yields. In particular, the addition of zirconia ceramic strips to the zirconia slurry can easily lead to sedimentation and uneven density, resulting in cracking during sintering.

Method used

A gel casting system was prepared by ball milling and mixing zirconia powder and water. Locust bean gum, sodium alginate and calcium chloride solution were added to form a three-dimensional network structure. Combined with an adhesive, a zirconia crucible blank was prepared and then cured and sintered.

Benefits of technology

The thermal shock stability and mechanical properties of zirconia crucibles have been improved, the upper limit of the service temperature has been increased, and they possess higher fracture toughness and bending strength, while reducing the difficulty of preparation and increasing the yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004968745670000081
    Figure BDA0004968745670000081
Patent Text Reader

Abstract

The application relates to a zirconia crucible and a preparation method thereof, and the preparation method comprises the following steps: S1, ball milling, zirconia powder and water are ball-mixed to obtain a zirconia slurry; S2, a gel injection molding system is prepared, sophora japonica gum and sodium alginate are mixed to prepare a gel injection molding system solution; S3, a pouring slurry is prepared, the zirconia powder and the zirconia slurry are uniformly mixed, then the adhesive and the gel injection molding system solution are uniformly mixed; S4, a crucible preliminary blank is prepared, the pouring slurry is used to prepare a zirconia crucible preliminary blank; and S5, curing and sintering, after the zirconia crucible preliminary blank is cured and sintered, a zirconia crucible product is obtained. The zirconia powder is used as the main body, a new, safe and non-toxic gel injection molding method is combined, the prepared zirconia crucible has excellent thermal shock stability, the upper limit of the use temperature is increased, has higher fracture toughness and bending strength, and can successfully smelt platinum, palladium, ruthenium, cesium and other platinum group noble metals and alloys thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of special ceramics preparation technology, and in particular to a zirconia crucible and its preparation method. Background Technology

[0002] Zirconia has a higher melting point than zirconium, reaching 2700℃, making it one of the best refractory materials in nature. While it has poor thermal conductivity, it has excellent electrical conductivity and strong corrosive properties; even when heated to 1900℃, it will not react with molten aluminum, iron, nickel, platinum, silicates, or acidic slag. Therefore, it can be used to manufacture crucibles for smelting precious metals, refractory tubes, heat-resistant glass, and heat-resistant enamels.

[0003] Currently, the preparation methods for zirconia crucibles are quite complex, including slip casting and hot pressing. However, the resulting zirconia crucibles exhibit poor thermal shock resistance and low reusability. To address this issue, manufacturers add zirconia ceramic strips to the zirconia slurry to improve thermal shock stability. However, these ceramic strips cannot be fixed in the slurry and tend to settle, requiring the introduction of additional materials to stabilize them. This increases the difficulty of crucible preparation and also leads to uneven crucible density due to the added ceramic strips, making them prone to cracking during sintering and resulting in low yield. Therefore, there is an urgent need to develop a new method for preparing zirconia crucibles that addresses the technical challenges of poor thermal shock resistance and complex preparation processes. Summary of the Invention

[0004] This invention provides a zirconium oxide crucible and its preparation method, which can solve the technical problems mentioned in the background section.

[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a zirconia crucible, comprising the following steps:

[0006] S1: Ball milling, mixing zirconium oxide powder and water in a certain proportion to obtain zirconium oxide slurry;

[0007] S2: Prepare a gel casting system by mixing locust bean gum and sodium alginate in a certain proportion to prepare a gel casting system solution;

[0008] S3: Prepare the casting slurry by mixing zirconium oxide powder and the zirconium oxide slurry evenly, and then adding the adhesive and the gel casting system solution and mixing evenly.

[0009] S4: Prepare crucible blanks by using the casting slurry to prepare zirconium oxide crucible blanks;

[0010] S5: Curing and sintering: After curing and sintering the zirconia crucible blank, the finished zirconia crucible is obtained.

[0011] As a preferred embodiment, in S2, the mixing ratio of locust bean gum and sodium alginate by weight is (2-3):1. This mixing ratio enables the slurry to possess good rheological properties. If the proportion of locust bean gum is too high, the slurry will be too thin, easily generating voids and air bubbles during the casting process, reducing the strength of the crucible, and may even lead to scrap due to excessive air bubbles; while if the proportion of sodium alginate is too high, the slurry will be too viscous, with poor fluidity, and the casting time will be too long, easily leading to premature solidification of the slurry before the casting is completed.

[0012] As a preferred embodiment, the locust bean gum and sodium alginate are heated to 80-90°C and then mixed to dissolve them into viscous liquids.

[0013] As a preferred embodiment, during the preparation of the S2 gel casting system, the locust bean gum and sodium alginate are mixed, and then a calcium chloride solution is added. On one hand, calcium chloride can promote the cross-linking between locust bean gum and sodium alginate molecules, enabling them to rapidly form a three-dimensional network structure, increasing viscosity and strength. On the other hand, because calcium chloride decomposes into calcium chloride dihydrate and calcium hydroxide at high temperatures, and calcium hydroxide further decomposes into calcium oxide, and calcium oxide is the most effective stabilizer for zirconia, it transforms zirconia from an unstable monoclinic phase to a stable tetragonal phase structure, and the density also changes from 5.65 g / cm³ in the monoclinic phase. 3 The 6.10 g / cm³ shift towards the tetragonal phase 3 This process enhances the mechanical properties of the prepared zirconia ceramic crucible, including its strength, fracture toughness, and seismic stability. This enhancement is based on the unique crystal structure of zirconia, which is not found in other ceramic materials. Furthermore, the main problem with the gel casting system composed of sodium alginate and locust bean gum is the high shrinkage rate of the green body during densification, which easily leads to deformation. The zirconia used in this invention, however, experiences a further increase in crystal density during high-temperature densification, thus slowing down the shrinkage of the green body and exhibiting a natural advantage over other ceramic materials.

[0014] As a preferred option, add 10-20 g·L of the calculated amount. -1 The amount of calcium chloride solution added will determine the quality of curing. Adding too much will shorten the curing time of the zirconia mixture slurry, which is very likely to cause premature curing during the casting process. Adding too little will prolong the curing time of the zirconia mixture slurry, resulting in incomplete curing of the green body in some areas.

[0015] As a preferred embodiment, in S3, the mixing ratio of the zirconia powder and the zirconia slurry, by weight, is (1.2-1.8):1. The mixing ratio of the zirconia powder and the zirconia slurry affects the viscosity of the slurry. The viscosity increases with the increase of the zirconia powder content, but if the proportion of zirconia powder is too high, the viscosity of the slurry will be too high to meet the casting requirements; if the zirconia powder content is too low, the density of the prepared zirconia crucible will be too low.

[0016] As a preferred embodiment, in step S3, the amount of adhesive added is 2%-5% of the slurry weight. When the adhesive is mixed at this ratio, it effectively prevents crucible collapse, exhibits good bonding performance, and does not deform during high-temperature drying. If the amount of adhesive added is too low, the bonding performance will be insufficient, easily resulting in low green strength and scrapping; if the amount of adhesive added is too high, it can easily increase the porosity inside the zirconia crucible during sintering, thereby affecting the mechanical properties.

[0017] As a preferred embodiment, in step S3, the amount of the gel casting system solution added is 10%-20% of the slurry weight. If the proportion of the gel system is too low, the molecular chains cannot be sufficiently cross-linked, resulting in low green strength and easy deformation of the green, leading to a decrease in yield. If the proportion of the gel system is too high, the molecular chains will cross-link with each other at a shorter length, which will also lead to low green strength. According to the formulation provided by this invention, the crucible green can have relatively ideal strength and toughness.

[0018] As a preferred embodiment, in step S4, the zirconia crucible blank is prepared by removing air bubbles from the casting slurry.

[0019] The present invention also provides a zirconium oxide crucible, which is prepared using the preparation method described in any of the above schemes.

[0020] The zirconia crucible and its preparation method provided by this invention use zirconia powder as the main component and combine it with a novel, safe, and non-toxic gel casting method. The resulting zirconia crucible exhibits excellent performance and can successfully melt platinum group metals such as platinum, palladium, ruthenium, and cesium, as well as their alloys. In particular, by compounding locust bean gum, sodium alginate, and sodium chloride in the gel casting system and further limiting the compounding ratio within a suitable range, the prepared zirconia crucible possesses excellent thermal shock resistance, an increased upper limit of operating temperature, and higher fracture toughness and flexural strength. Detailed Implementation

[0021] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0022] This invention provides a method for preparing a zirconium oxide crucible, comprising the following steps:

[0023] S1: Ball milling: Zirconia powder and water are added to a ball mill containing ball stones in a weight ratio of (70-80):(30-20) and ball milled for 12-16 hours to obtain a zirconia slurry with a particle size of 3.6-4.5μm.

[0024] The zirconia powder is yttrium-stabilized 3Y zirconia powder, and the spheres are zirconia spheres or alumina spheres, preferably zirconia spheres, which can reduce the introduction of other impurities. Alternatively, alumina spheres with a hardness higher than zirconia can be selected. The zirconia powder and water can be ground into a zirconia slurry with less impurity introduction.

[0025] S2: To prepare the gel casting system, heat the locust bean gum and sodium alginate to 80-90℃ and mix them evenly in a weight ratio of (2-3):1. Then add 10-20 g·L⁻¹ of the calculated amount. -1 A calcium chloride solution is prepared to form a 1%-5% gel casting system solution. The amount of calcium chloride solution added is 20-40% of the mass of the mixture of locust bean gum and sodium alginate.

[0026] S3: Prepare the casting slurry by mixing zirconium oxide powder and the zirconium oxide slurry at a weight ratio of (1.2-1.8):1, adding 2%-5% of the slurry weight of adhesive and 10%-20% of the gel casting system solution, cooling to 20-30℃, and mixing evenly in a mixer.

[0027] The adhesive is made of one or a mixture of two of polyvinyl alcohol and polyethylene glycol.

[0028] S4: To prepare the crucible blank, heat the zirconia casting slurry to 80-90℃, then place it in a vacuum mixer at a constant temperature of 80-90℃ and stir for 60-90 minutes to remove air bubbles. Pour the defoamed slurry into the crucible mold under a pressure of 0.3-0.6 MPa, and hold the pressure for 5-10 minutes after filling. Place the mold in a cold water bath at 20-30℃ for 20-30 minutes, then demold to obtain the zirconia crucible blank.

[0029] S5: Curing and sintering. Place the zirconia crucible blank in a curing room at 70-80℃ for 24-36 hours, and then place the cured zirconia crucible in a kiln at 1480-1530℃ for sintering for 36-48 hours to obtain the finished product.

[0030] The locust bean gum used in the gel casting system of this invention is a galactomannan. The polymer backbone is composed of mannose, and the side chains are galactose, with a mannose to galactose ratio of 4:1. Locust bean gum can be completely dissolved in water at 80°C to form a viscous liquid. The viscosity does not change when the pH is between 3.5 and 9, but decreases outside this range.

[0031] Sodium alginate is a polysaccharide carbohydrate extracted from brown algae such as kelp or Sargassum. It is a linear polymer composed of 1,4-poly-β-D-mannuronic acid and α-L-guluronic acid, and is one of the derivatives of alginate. As a hydrophilic polymer, sodium alginate exhibits the general characteristics of polymers, and its water solubility also displays the solution properties characteristic of polymer solutions. An important feature of sodium alginate solutions is their high viscosity.

[0032] Locust bean gum interacts with sodium alginate, increasing its viscosity and forming a gel within a specific ratio range. However, before gelation occurs, both locust bean gum and sodium alginate must be dissolved in water at 80-90℃ to form a viscous liquid. Adjusting the ratio between the two allows the long-chain structures of locust bean gum and sodium alginate to intertwine and form a three-dimensional network structure.

[0033] Furthermore, when locust bean gum dissolves in water, its molecules automatically aggregate to form a double helix structure. The two molecular chains form parallel helices in a right-handed manner. Upon adding calcium chloride, calcium ions initiate polymerization and cross-linking between the double helices. Calcium ions promote intramolecular cross-linking, stabilize the double helix structure, and accelerate the formation of a three-dimensional network structure. Sodium alginate can undergo rapid ion exchange reactions with divalent metal ions (except magnesium and mercury) to generate alginate gels, with the gel film formed with calcium chloride exhibiting the greatest strength. In an aqueous solution of sodium alginate and calcium chloride, due to the relatively large molecular weight and long molecular chains of alginate, the polymer chains form random coils that easily entangle with each other. This entanglement increases the size of the flow units, increasing resistance to flow and thus leading to a rapid increase in viscosity. This is mainly because when alginate reacts with calcium ions, the calcium ions act as bridges between two adjacent uronic acid carboxyl groups, leading to intermolecular cross-linking, increasing molecular volume and entanglement, thus increasing viscosity. Therefore, adding a small amount of calcium ions can improve the thickening effect.

[0034] Since both locust bean gum and sodium alginate can react with calcium chloride solution to form gels, in Ca... 2+Under certain conditions, sodium alginate and locust bean gum exhibit a synergistic gelling effect, are relatively stable, and have high strength.

[0035] The present invention will be further described in detail below with reference to embodiments. It should also be understood that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below.

[0036] Example 1

[0037] This embodiment provides a method for preparing a zirconium oxide crucible, including the following steps:

[0038] S1: Ball milling: Zirconia powder and water are added to a ball mill containing ball stones at a weight ratio of 75:25 and ball milled for 12 hours to obtain a zirconia slurry with a particle size of 4.0 μm.

[0039] S2: To prepare the gel casting system, heat the locust bean gum and sodium alginate to 80°C, mix them evenly in a weight ratio of 3:1, and then add 10 g·L -1 A calcium chloride solution was added at a rate of 40% of the mass of the mixture of locust bean gum and sodium alginate to prepare a 2% gel casting system solution.

[0040] S3: Prepare the casting slurry by mixing zirconium oxide powder and zirconium oxide slurry at a weight ratio of 1.5:1, adding 2% of the slurry weight of adhesive polyvinyl alcohol and 15% of the gel casting system solution, cooling to 25°C, and mixing evenly in a mixer.

[0041] S4: To prepare the crucible blank, heat the zirconia casting slurry to 80°C, then place it in a vacuum mixer at a constant temperature of 80°C and stir for 60 minutes to remove air bubbles. Pour the defoamed slurry into the crucible mold under a pressure of 0.3 MPa, and hold the pressure for 5 minutes after filling. Place the mold in a 20°C cold water bath for approximately 25 minutes, then demold to obtain the zirconia crucible blank.

[0042] S5: Curing and sintering. Place the zirconia crucible blank in an 80℃ curing room for 24 hours, and then place the cured zirconia crucible in a 1500℃ kiln for sintering for 36 hours to obtain the finished product.

[0043] Example 2

[0044] This embodiment provides a method for preparing a zirconium oxide crucible, including the following steps:

[0045] S1: Ball milling: Zirconia powder and water are added to a ball mill containing ball stones at a weight ratio of 80:20 and ball milled for 15 hours to obtain a zirconia slurry with a particle size of 4.2μm.

[0046] S2: To prepare the gel casting system, heat the locust bean gum and sodium alginate to 85°C, mix them evenly in a 2:1 weight ratio, and then add 20 g·L⁻¹. -1 A calcium chloride solution was added at a rate of 20% of the mass of the mixture of locust bean gum and sodium alginate to prepare a 5% gel casting system solution.

[0047] S3: Prepare the casting slurry by mixing zirconium oxide powder and zirconium oxide slurry at a weight ratio of 1.3:1, adding 4% of the slurry weight of the adhesive polyethylene glycol and 20% of the gel casting system solution, cooling to 30°C, and mixing evenly in a mixer.

[0048] S4: To prepare the crucible blank, heat the zirconia casting slurry to 80°C, then place it in a vacuum mixer at a constant temperature of 80°C and stir for 90 minutes to remove air bubbles. Inject the defoamed slurry into the crucible mold under a pressure of 0.3 MPa, and hold the pressure for 5 minutes after filling. Place the mold in a 25°C cold water bath for 30 minutes, then demold to obtain the zirconia crucible blank.

[0049] S5: Curing and sintering. The zirconia crucible blank is placed in an 80℃ curing room for 24 hours, and the cured zirconia crucible is placed in a kiln at 1530℃ for sintering for 36 hours to obtain the finished product.

[0050] Example 3

[0051] This embodiment provides a method for preparing a zirconium oxide crucible, including the following steps:

[0052] S1: Ball milling: Zirconia powder and water are added to a ball mill containing ball stones at a weight ratio of 70:30 and ball milled for 15 hours to obtain a zirconia slurry with a particle size of 3.9 μm.

[0053] S2: To prepare the gel casting system, heat the locust bean gum and sodium alginate to 90°C, mix them evenly in a weight ratio of 2.5:1, and then add 15 g·L -1 A calcium chloride solution was added at a rate of 30% of the mass of the mixture of locust bean gum and sodium alginate to prepare a 4% gel casting system solution.

[0054] S3: Prepare the casting slurry by mixing zirconium oxide powder and zirconium oxide slurry at a weight ratio of 1.8:1, adding 5% of the slurry weight of the adhesive polyethylene glycol and 10% of the gel casting system solution, cooling to 30°C, and mixing evenly in a mixer.

[0055] S4: To prepare the crucible blank, heat the zirconia casting slurry to 90°C, then place it in a vacuum mixer at a constant temperature of 90°C and stir for 90 minutes to remove air bubbles. Inject the defoamed slurry into the crucible mold under a pressure of 0.6 MPa, and hold the pressure for 10 minutes after filling. Place the mold in a 25°C cold water bath for 30 minutes, then demold to obtain the zirconia crucible blank.

[0056] S5: Curing and sintering. The zirconia crucible blank is placed in an 80℃ curing room for 24 hours, and the cured zirconia crucible is placed in a kiln at 1530℃ for sintering for 36 hours to obtain the finished product.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is that the locust bean gum in the gel casting system is replaced with gelatin, while the other methods and steps are the same.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that sodium alginate in the gel casting system is replaced with ammonium alginate, while the other methods and steps are the same.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 1 is that the mixing ratio of locust bean gum and sodium alginate is 1:1, while the other methods and steps are the same.

[0063] Comparative Example 4

[0064] The difference between this comparative example and Example 1 is that the mixing ratio of locust bean gum and sodium alginate is 4:1, while the other methods and steps are the same.

[0065] Comparative Example 5

[0066] The difference between this comparative example and Example 1 is that calcium chloride solution is not added to the gel casting system, while the other methods and steps are the same.

[0067] Comparative Example 6

[0068] This comparative example uses a commercially available slurry-cast zirconia crucible.

[0069] Comparative Example 7

[0070] This comparative example uses a commercially available hot-pressed zirconia crucible.

[0071] The ten zirconia crucibles provided in Examples 1 to 3 and Comparative Examples 1 to 7 were tested for the following performance parameters, and the test results are shown in Table 1:

[0072] Thermal shock resistance test method: The Chinese straight brick water quenching method (YB 376) was adopted. The heated end face of the straight brick ((200~230mm)×(100~150mm)×(50~100mm)) was inserted 50mm into a furnace preheated to 1100℃ and held for 20min. Then it was quenched in water at room temperature for 3min and then dried. The thermal shock resistance was characterized by the number of thermal cycles in which half of the heated end face was damaged.

[0073] Table 1 Performance and Comparison of Zirconia Crucibles

[0074]

[0075] According to the table above, the test results of each embodiment and comparative example show that the gel injection molding system in the embodiments, by compounding locust bean gum, sodium alginate and sodium chloride, and further limiting the compounding ratio within a suitable range, has a significantly improved thermal shock stability and an increased upper limit of operating temperature. Compared with the comparative example, it has higher fracture toughness and bending strength.

[0076] In Comparative Example 1, gelatin and sodium alginate were used in combination. Because gelatin has a low coagulation temperature, it needs to be cooled to below 10°C to form a gel. Furthermore, gelatin has the best gelation effect in a slightly acidic environment. In this comparative example, the cooling temperature and neutral environment are not conducive to the coagulation of gelatin, which results in its low strength and fracture toughness.

[0077] In Comparative Example 2, a mixture of locust bean gum and ammonium alginate was used. Ammonium alginate is alkaline, and the optimal pH of locust bean gum gel is between 5.4 and 7.0. Therefore, it will affect the performance of locust bean gum gel, and thus affect the mechanical properties of zirconia crucible.

[0078] In Comparative Examples 3 and 4, improper ratios of locust bean gum and sodium alginate both resulted in a decrease in the density of the zirconia crucible and a decrease in the yield.

[0079] In Comparative Example 5, the gel casting system only uses a combination of locust bean gum and sodium alginate, lacking calcium chloride, which weakens the strength and viscosity of the gel casting system, thus affecting the mechanical properties of the crucible.

[0080] The zirconia crucibles prepared by commercially available slurry casting and hot die casting methods in Comparative Examples 6 and 7 showed significantly lower thermal shock stability and other parameters compared to the examples.

[0081] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention. The embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a zirconia crucible, characterized in that, Includes the following steps: S1: Ball milling, mixing zirconium oxide powder and water in a certain proportion to obtain zirconium oxide slurry; S2: Prepare a gel casting system by mixing locust bean gum and sodium alginate in a certain proportion to prepare a gel casting system solution; S3: Prepare the casting slurry by mixing zirconium oxide powder and the zirconium oxide slurry evenly, and then adding the adhesive and the gel casting system solution and mixing evenly. S4: Prepare crucible blanks by using the casting slurry to prepare zirconium oxide crucible blanks; S5: Curing and sintering, the zirconia crucible blank is cured and sintered to obtain the finished zirconia crucible; In the preparation of the S2 gel casting system, after mixing the locust bean gum and sodium alginate, a calculated amount of 10-20 g•L is added. -1 Calcium chloride solution.

2. The method for preparing the zirconia crucible according to claim 1, characterized in that, In S2, the mixing ratio of locust bean gum and sodium alginate by weight is (2-3):

1.

3. The method for preparing the zirconia crucible according to claim 1, characterized in that, In step S2, the locust bean gum and sodium alginate are heated to 80-90°C and then mixed.

4. The method for preparing the zirconia crucible according to claim 1, characterized in that, In S3, the mixing ratio of the zirconium oxide powder and the zirconium oxide slurry by weight is (1.2-1.8):

1.

5. The method for preparing the zirconia crucible according to claim 1, characterized in that, In S3, the amount of adhesive added is 2%-5% of the weight of the slurry.

6. The method for preparing the zirconia crucible according to claim 1, characterized in that, In S3, the amount of the gel casting system solution added is 10%-20% of the weight of the slurry.

7. The method for preparing the zirconia crucible according to claim 1, characterized in that, In step S4, the zirconia crucible blank is prepared by removing air bubbles from the casting slurry.

8. A zirconium oxide crucible, characterized in that, Prepared using the preparation method according to any one of claims 1-7.

Citation Information

Patent Citations

  • Dropping pill with sodium alginate and locust bean gum as capsule wall material, and its production technology

    CN104337780A

  • Method for molding yttrium oxide partially stabilized zirconium oxide ceramic crucible through gel casting

    CN108101534A

  • Liquid molding method for ceramic grinding ball

    CN108298959A